KOSAKATA BERLADANG SUKU PASER DI KECAMATAN LONG IKIS: KAJIAN SEMANTIK - Nurul Masfufah (tuahtalino, 2019)
The research on the farming vocabulary of the Paser ethnic is important as a form of preservation and inventory of the vocabulary. This study aims to describe the dictions and meaning of the farming vocabulary of the Paser ethnic in the Long Ikis District. This study uses lexical semantic studies to analyze the research data. The data were collected from informants through note-taking techniques and interviews with voice recorder tools. Analysis of research data using descriptive analysis techniques includes the analysis of linguistic (semantic) data. The data analysis technique in this study used the descriptive analysis, namely by analyzing linguistic (semantic) data. The data analysis model used is an interactive model analysis consisting of three components of analysis, namely data reduction, data presentation, and drawing conclusions. Based on the results of the research and discussion, there were 35 farming vocabularies of the Paser ethnic which consisted of five classifications, namely (a) pre-farming process totaling 9 vocabulary, (b) tools to open the fields consist of 4 vocabularies, (c) the process of planting and caring consists of 4 vocabularies, (d) the process of harvesting and post-harvestingconsist of 9 vocabularies, and (e) tools for harvesting and post-harvestingconsist of 9 vocabularies. The analysis of the concept of semantic meaning is also associated with the cultural meaning of the local community because it can clarify the meaning of the farming vocabularies.